Analisis Pengaruh Laba Bersih, Leverage Dan Pertumbuhan Penjualan Terhadap Kinerja Perusahaan (Studi Kasus Pada Indomaret Medan Tahun 2010-2023) - Mey Yanra Sipayung; Aria Masdiana Pasaribu; Sri Liniarti (Fakultas Ekonomi Universitas Al-Azhar Medan, 2026)
This research focuses on examining how Net Income, Debt to Equity Ratio (DER), and Sales Growth influence Net Profit Margin (NPM) at Indomaret Medan from 2010 to 2023. NPM serves as the primary measure to evaluate how profitable the business is. The study uses a quantitative method with multiple linear regression analysis, aided by SPSS version 23 software. The findings indicate that separately, Net Income and DER negatively impact NPM significantly, while Sales Growth does not have a noteworthy effect. However, when looking at all three factors together, Net Income, DER, and Sales Growth significantly affect NPM. The determination coefficient shows that a large portion of the changes in NPM can be accounted for by these three independent variables, whereas the rest is affected by other elements not included in this research. These results signify that the structure of net income and the levels of debt are crucial in influencing a company's profitability, while sales growth alone does not make a significant difference without effective cost management and sound managerial strategies.